THE SITUATION OF ANXIETY, DEPRESSION, AND THE RESULTS OF CARE, PROVIDE INFORMATION, AND CONSULTATIONS FOR IVF COUPLES AT CAN THO CITY OBSTETRICS AND GYNECOLOGY HOSPITAL 2020-2021 (Vietnam Journal of Community Medicine, 2022)
Objectives: To determine the prevalence of anxiety and depression in infertile couples undergoing IVF treatment, and evaluate the results of counseling care for infertile couples undergoing IVF treatment at the Can Tho city Obstetrics and Gynecology Hospital. Subjects and methods: A cross-sectional descriptive study of 139 couples at Can Tho Obstetrics and Gynecology Hospital during the period from November 1, 2020 to April 30, 2021. Results: There were 53 patients with symptoms of anxiety and real anxiety, accounting for 19.0%. In which, the status of having symptoms of anxiety to real anxiety in the wife is 19 (14.0%) and in the husband is 14 (5.0%). 52 patients had real depressive and depressive symptoms, accounting for 18.7%. In which, there are 56 couples (accounting for 40.3%) with symptoms of anxiety, depression to anxiety, real depression. This ratio is equivalent to about 20% of the couples in the study of Jolijn (2016). The percentage of women with real anxiety and depression (1.8% and 2.2%) is higher than that of men (1.2% and 0%). The proportion of wives with symptoms of anxiety and depression (12.2% and 14.0%) is higher than that of husbands (4.0% and 6.1%). The psychological intervention method is the Mind-Body Program, applied by the nurses of the HTSS clinic on 40 couples (71.4%) with anxiety and depression through the process and electrical approach. Telephone combined with direct consultation via Zoom. After the intervention, there were 11 men and 21 women whose anxiety symptoms returned to normal. Besides, there are 3 men, 5 women with real anxiety only have anxiety symptoms, there is a significant difference in the mean of anxiety patients before and after the intervention with Sig. (2 sides) < 0.05. There are 8 men and 4 women whose depressive symptoms become normal, 2 women with real depression only have depressive symptoms, there is a significant difference in the mean of depressed patients before and after the intervention. with Sig. (2 sides) < 0.05. The percentage of unsatisfied patients decreased from 80.0% to 5.0%. Meanwhile, the satisfaction level increased from 2.5% to 87.5%. Satisfaction difference was statistically significant in the 40 intervention couples.
Keywords: Anxiety, depression, IVF treatment.